Studi Komparasi Peta Bahaya Kekeringan Meteorologi dan Hidrologi WS Pemali Comal - Primadita, Brigita Diaz; Utami, Nirmaya Arti; Utama, Riksa Nugraha; Levina; Radhika; Pohan, Dasniari; Rizqullah, Hirzi (Jurnal Teknik Sumber Daya Air, 2023)
The Pemali-Comal River Basin experienced a very massive impact due to drought, considering the large area of land used for agriculture. Therefore, an effective drought mitigation is needed, one of which is developing a hazard map that includes spatial analysis and the severity degree of the drought. This study aims to compare the spatial distribution of meteorological and hydrological drought hazards in the Pemali-Comal River Basin. Meteorological drought can identify areas that naturally experience a water deficit due to rain, while hydrological drought can indicate areas that experience a surface flow deficit. Drought hazard mapping was carried out using condition classification using the Standardized Precipitation Index and Standardized Runoff Index on 67 rain gauges and 16 streamflow gauges throughout 1990-2021. More than half of the total Pemali Comal River Basin area is at a high-very high danger level (70% meteorological drought and 50% hydrological drought). Regarding the danger of meteorological drought, the majority of areas with a very high level of danger are in the eastern part of the river region, namely Pemalang Regency , Pekalongan Regency, and parts of Batang Regency. Meanwhile, from hydrological drought, the northern coastal areas of the Pemali-Comal WS, especially in the north of Brebes Regency, Tegal City, north of Pemalang Regency and Pekalongan City tend to have very high levels of danger. The hydrological drought (showing surface water deficit) in the Pemali Comal River Basin are caused by athropogenic factors which can be seen from the distribution of land use. Therefore, it is recommended to carry out mitigation such as rainwater harvesting, creating water reservoirs, and reforesting areas that have a very high risk of surface water drought, especially in the northern part of the Pemali-Comal River Basin.